2006
DOI: 10.1016/j.jhsb.2005.11.003
|View full text |Cite
|
Sign up to set email alerts
|

Sonographically Assisted Percutaneous Release of the A1 Pulley: A New Surgical Technique for Treating Trigger Digit

Abstract: This study introduces a sonographically assisted percutaneous technique for releasing trigger digits which provides direct visualization of the release and avoids the risks of incomplete release and injury to adjacent neurovascular structures associated with other percutaneous release techniques. The "safe zone" and an estimate of the size of the A1 pulley were determined in a separate cadaver study. We then used these landmarks in a prospective clinical study of 107 digits in 83 consecutive patients treated b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

11
107
1
3

Year Published

2008
2008
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 80 publications
(122 citation statements)
references
References 32 publications
11
107
1
3
Order By: Relevance
“…Similar results were reported in previous studies using clinical observations or telephone interviews. 7,9,11,13,[28][29][30] Subsequently, each joint's ROM showed improvement. Although most studies reported that the majority of trigger digit patients had regained full or normal ROM after treatment, 1,7,9,11,13,[28][29][30][31][32] the recovery rate of the workspace and joint ROM in this study was 87-92% of the performances of the intact hand 12 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 94%
See 4 more Smart Citations
“…Similar results were reported in previous studies using clinical observations or telephone interviews. 7,9,11,13,[28][29][30] Subsequently, each joint's ROM showed improvement. Although most studies reported that the majority of trigger digit patients had regained full or normal ROM after treatment, 1,7,9,11,13,[28][29][30][31][32] the recovery rate of the workspace and joint ROM in this study was 87-92% of the performances of the intact hand 12 weeks postoperatively.…”
Section: Discussionmentioning
confidence: 94%
“…7,9,11,13,[28][29][30] Subsequently, each joint's ROM showed improvement. Although most studies reported that the majority of trigger digit patients had regained full or normal ROM after treatment, 1,7,9,11,13,[28][29][30][31][32] the recovery rate of the workspace and joint ROM in this study was 87-92% of the performances of the intact hand 12 weeks postoperatively. This might be because ROM evaluations in previous studies were based on direct observations or the clients' self-reported outcomes, 1,7,11,13,[28][29][30][31][32] so the 10% difference in full or normal ROM might not have been detected visually.…”
Section: Discussionmentioning
confidence: 94%
See 3 more Smart Citations